Mulher no volante, perigo constante? Um estudo sobre trabalhadoras no transporte coletivo por ônibus no interior paulista - Celestini, Sarah (2015)
This research aimed to study the work of women in public transportation by bus, specifically those that hold positions of drivers and collectors in two companies in the cities of Araraquara and São Carlos, São Paulo. The general objective was to analyze the work of these women in a predominantly male environment and check the sociability of those working in this environment, and the ways how they deal with it in their daily lives. For the research, documentary sources, observations of work on buses, terminals were used and 12 in-deep interviews were applied with the workers of these companies. The relation between workers and the company was obtained that there is no differentiation between men and women, occurring only differentiation between the posts, however the working underscore the need for drivers to have to be sure of themselves and prove they are as capable as men run driving the bus. Colleagues, workers claim that the relationship is positive and in some situations should "take a joke" what they say. The "take a joke" was considered here as a self-defense mechanism, as well as the isolation and distrust in this workspace were seen as internal forms of protection to continue carrying out the activities. The presence of the harassment was found, both moral and sexual harassment attempts as well, which again lead them to use the mechanisms available to them, among them the serious and masculine stance to avoid sung. The emotional work was also seen in the activity, being reflected by stress and exhaustion as a result of dealing with passengers, colleagues and look after the house, occurring as a third working day for drivers and collectors.